War, Clausewitz and the Trinity - Waldman, Thomas (Ashgate Pub., 2013)
In this book, Waldman explores Clausewitz's central theoretical device for understanding war - the 'remarkable trinity' of politics, chance, and passion. Through an in-depth reinterpretation of On War and Clausewitz's other writings, conducted through the prism of the trinity and in the light of contemporary scholarship on war.